Landscape‐scale fuel treatment and wildfire impacts on carbon stocks and fire hazard in California spotted owl habitat. Issue 1 (19th January 2017) - Chiono, Lindsay A.; Fry, Danny L.; Collins, Brandon M.; Chatfield, Andrea H.; Stephens, Scott L.
Abstract: Forest managers are challenged with meeting numerous demands that often include wildlife habitat and carbon (C) sequestration. We used a probabilistic framework of wildfire occurrence to (1) estimate the potential for fuel treatments to reduce fire risk and hazard across the landscape and within protected California spotted owl ( Strix occidentalis occidentalis ) habitat and (2) evaluate the consequences of treatments with respect to terrestrial C stocks and burning emissions. Silvicultural and prescribed fire treatments were simulated on 20% of a northern Sierra Nevada landscape in three treatment scenarios that varied in the land area eligible for treatment. Treatment prescriptions varied with topography, vegetation characteristics, and ownership. We then simulated many wildfires in the treated and untreated landscapes. Additional simulations allowed us to consider the influence of wildfire size on estimated emissions. Treatments constrained to the land area outside of spotted owl activity centers reduced the probability of burning and potential fire intensity within owl habitat and across the landscape relative to no‐treatment scenarios. Allowing treatment of the activity centers achieved even greater fire hazard reductions within the activity centers. Treatments also reduced estimated wildfire emissions of C by 45–61%. However, emissions from prescribed burning exceeded simulated reductions in wildfire emissions. Consequently, all treatment scenarios resulted in higher C emissions than the no‐treatment scenarios. Further, for wildfires of moderate size (714–2133 ha), the treatment scenarios reduced the C contained in live tree biomass following simulated wildfire. When large wildfires (8070–10, 757 ha) were simulated, however, the treatment scenario retained more live tree C than the no‐treatment scenario. Our approach, which estimated terrestrial C immediately following wildfire, did not account for long‐term C dynamics, such as emissions associated with post‐wildfire decay, C sequestration by future forest growth, or longer‐term C sequestration in structural wood products. While simulated landscape fuel treatments in the present study reduced the risk of uncharacteristically severe wildfire across the landscape and within protected habitat, the C costs of treatment generally exceeded the C benefits.